PENGGUNAAN TEPUNG KULIT BUAH KAKAO PADA PAKAN PENGARUHNYA TERHADAP PERTUMBUHAN DAN PRODUKSI GURAMI - Sukardi Sukardi; Senny Helmiati; Yunita Wulandari (Jurnal Perikanan Universitas Gadjah Mada, 2012)
The aims of the research were to observe (1) utilization of cocoa pod husk meal to fish feed especially for carbohydrate source (2) effect of substitution rice bran by cocoa pod husk meal on growth and product of giant goramy (3) find the substitution doses of rice bran by cocoa pod husk meal on feed which could give better influence on giant goramy growth. The research was done for 8 months in Fisheries Research Station Laboratory, Agriculture Faculty Gadjah Mada University. Research was conduct by cultured of giant goramy on fibre tank, for 60 days. There were 5 treatmens substitution dose (20, 40, 60, and 80%) and control (comercial feed) with 3 replications. During cultured the tank were irrigated and the fish were fed 3% of body weight 3 times a day. The result showed that cocoa pod husk meal can substitute rice bran on giant goramy feed. Substitution rice bran by cocoa pod husk meal on fed not significantly affect on the growth, product and survival rate of giant goramy, but significant affected on buoyancy of feed. Giant goramy were feeding by comercial feed had growth and product better than feeding by artificial feed.